Association of socioeconomic status, consanguinity and congenital ophthalmological anomalies - Abbas, Sana; Muzaffar, Waqar (Majalah Kesehatan Indonesia, 2025)
This cross-sectional analytical study was carried out at Tertiary Care Institute from September 2020 to January 2021 in Pakistan. All pediatric patients with congenital ophthalmological abnormalities, scheduled for ophthalmological surgeries or examinations born with uncomplicated pregnancies and parturition were included in the study. Since government basic pay scales are fixed, it gives an estimation of average income, therefore, these were employed to determine socioeconomic status. If a couple had a history of infertility and complicated pregnancy or parturition, they were excluded from the study. The mean maternal and paternal age was recorded to be 23.86±5.4 and 27.07±9.6 respectively. We studied 184 children with congenital abnormalities, with a ratio of 126 (68.5%) males and 58 (31.5%) females. The median age in years was reported to be 2.0 years with a 25% inter-quartile range of 1.0. The most common congenital abnormality observed was congenital cataract, reported in 66/184 (35.9%) of the children, followed by squint present in 17/184 (9.24%) children and retinoblastoma was reported in 12/184 (6.52%) of children. Parents from the lower middle income group were more likely to have undergone inter-family marriages compared to the middle and upper middle income group, respectively (80% vs. 62% vs. 20%). There is an evidence that cataracts and retinoblastoma in the studied Pakistani population are dependent on the age of patients and consanguinity and later, in turn caused by socioeconomic status. It is highly unlikely to establish a link that glaucoma is caused by consanguinity and socioeconomic status. Congenital malformations were observed in a greater proportion of pediatric patients whose parents had consanguineous marriages than non-consanguineous parents. Congenital anomalies in ophthalmological patients are more common and are on the rise consistently due to a lack of awareness both in numbers and spectrum. The congenital anomalous patient needs a team effort for the disease management. The psychological impact on the parents of the affected child is significant and they need prolonged psychological support to prepare themselves to fight with prolonged illness and care.